Nigerian students' perceptions on student-centered learning (SCL) - T.B., Jimoh; Mohd Yusoff, Nurahimah (2010)
Learning is essential in human’s life as it is evidenced by the transformation of biological being to a knowledgeable being via learning process. It is now a global concern to device an educational pedagogy that can support long life learning that can enhance the productivity and creativity of the learner. This led to the adoption of the Student-Centered Learning (SCL)curriculum which has contributed immensely in this regard. Nigerian educational system is characterized with the passive traditional teacher-centered lecture method; which renders the students inactive. There have been series of probing question on such an outdated learning approach. Therefore, this paper presents the findings of the study carried out to investigate the perceptions of Nigerian students in some Malaysian public Universities about the SCL approach in terms of the perceived benefits and satisfaction. The study involves 222 students from four public Universities in Malaysia using questionnaire as the survey instrument which was developed for the two constructs (perception (benefits) and satisfaction). The data was analyzed using descriptive statistics. The findings of the study showed that the surveyed students perceived SCL to be of great advantages in their learning process and they were satisfied with the approach especially the collaborative form of SCL.